GANGGUAN SKIZOAFEKTIF DENGAN KOMORBIDITAS DIABETES MELITUS : SEBUAH TINJAUAN PUSTAKA - ARIRAHMAYANTI, I GUSTI AYU EKA; ARDANI, I GUSTI AYU INDAH; SUHARDI, MUHAMAD (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2024)
The prevalence rate is that individuals with schizophrenia and schizoaffective disorder have more than twice the risk of developing type 2 diabetes mellitus (T2DM) compared to the general population. People on the schizophrenia spectrum are genetically predisposed to type II diabetes, accompanied by weight gain as a side effect of treatment, which is a risk factor for developing type 2 diabetes, which will worsen medical outcomes and mortality rates. This literature review involves 21 journal and book literature from the last 10 years regarding schizoaffective with comorbid diabetes mellitus. Different data sources and manual literature search methods were used to find related articles. The increase in comorbid DM in schizoaffective is related to mitochondrial dysfunction, the presence of shared susceptibility genes, and side effects of therapy. Functional proteins translated from shared genetic susceptibility genes are known to regulate neuronal development in the brain and insulin in the pancreas through several key cascades. Quetiapine, Ziprasidone, aripiprazole, and lurasidone have a lower metabolic risk profile. Olanzapine, clozapine and valproate are a high risk group for metabolic disorders. A much lower risk of DM was associated with lithium, lamotrigine, oxcarbazepine and bupropion monotherapy, single class selective serotonin reuptake inhibitor (SSRI) therapy and some drug combinations containing bupropion and SSRIs. Rational use of antipsychotics, metabolic monitoring and pharmacological and lifestyle modifications can also be carried out to reduce the risk of DM. Psychosis is a known risk factor for increasing metabolic syndrome. The existence of shared susceptibility genes between schizophrenia and DM, mitochondrial dysfunction, side effects of antipsychotic medication, antidepressants, mood stabilizers play a role in this. ABSTRAKAngka prevalensi individu penderita skizofrenia dan gangguan skizoafektif mempunyai risiko lebih dari dua kali lipat mengalami diabetes melitus tipe 2 (DMT2) dibandingkan populasi umum. Orang dengan spektrum skizofrenia secara genetik cenderung mengalami diabetes tipe II disertai peningkatan berat badan sebagai efek samping pengobatan merupakan faktor risiko berkembangnya diabetes tipe 2 yang akan memperburuk luaran medis dan tingkat mortalitas. Tinjauan literatur ini melibatkan 21 literatur jurnal dan buku 10 tahun terakhir mengenai skizoafektif dengan komorbiditas diabetes melitus. Sumber data yang berbeda dan metode pencarian literatur manual digunakan untuk menemukan artikel yang berkaitan. Peningkatan komorbid DM pada skizoafektif berkaitan dengan disfungsi mitokondria, adanya gen kerentanan bersama, serta efek samping terapi. Protein fungsional yang ditranslasi dari gen kerentanan genetik bersama diketahui mengatur perkembangan saraf di otak dan insulin di pankreas melalui beberapa kaskade utama. Quetiapine, Ziprasidone, aripiprazole, dan lurasidone memiliki profil risiko metabolik yang lebih rendah. Olanzapine, clozapine dan valproat merupakan kelompok risiko tinggi terjadinya gangguan metabolisme. Risiko DM jauh lebih rendah dikaitkan dengan monoterapi litium, lamotrigin, oxcarbazepine dan bupropion, terapi kelas tunggal inhibitor reuptake serotonin selektif (SSRI) dan beberapa kombinasi obat yang mengandung bupropion dan SSRI. Penggunaan antipsikotik yang rasional, pemantauan metabolik serta modifikasi farmakologis dan gaya hidup juga dapat dilakukan untuk mengurangi risiko DM. Psikosis merupakan faktor risiko yang diketahui meningkatkan sindrom metabolik. Adanya gen kerentanan bersama antara skizofrenia dan DM, disfungsi mitokondria, efek samping pengobatan antipsikotik, antidepresan, penstabil suasana hati berperan dalam hal tersebut.